Reducing Waste Collection Through Ecobrick Become A Wise Solution In Heroes Village - Faried, Annisa Ilmi; Sembiring, Rahmad; Wahyuni, Neng Sri (Universitas Negeri Medan, 2023)
Community activities that adopt a mutual cooperation system and joint management of inorganic waste have the potential to be used as an effective and targeted product in terms of waste management. Recycling inorganic waste as one way to achieve this goal. This pattern will make empowerment activities a major breakthrough in government programs, especially in circular economy activities to reduce the degree of organic waste contamination, which has been more critical in dealing with inorganic waste and public apathy towards waste management and the circular economy. As a consequence of this, efforts to promote empowerment will be a major focus of progress in government initiatives. Ecobrik is a new product developed with the aim of reducing the amount of various forms of inorganic waste and contaminants in the soil. The product name comes from the word “eco”, which refers to inorganic waste and contaminants. Increasing community empowerment through the use of ecobricks has the potential to reduce the level of community dependence on cement products and other materials. This is one of the potential benefits of using ecobricks. Utilization of ecobricks will provide space for the formation of a circular economy, as well as green spaces that will supply oxygen and ensure that the water cycle continues to rotate and change. Increasing community empowerment through the use of ecobricks has the potential to reduce the level of community dependence on cement products and other materials. This is one of the potential benefits of using ecobricks. The use of eco-bricks will provide space for the formation of a circular economy, as well as green spaces that will supply oxygen and ensure that the water cycle continues to rotate and change. Increasing community empowerment through the use of ecobricks has the potential to reduce the level of community dependence on cement products and other materials. This is one of the potential benefits of using ecobricks. The use of eco-bricks will provide space for the formation of a circular economy.